Factors Associated With Forensic Nurses Offering HIV nPEP Status Post Sexual Assault. (September 2015) - Draughon, Jessica E.; Hauda, William E.; Price, Bonnie; Rotolo, Sue; Austin, Kim Wieczorek; Sheridan, Daniel J.
Nonoccupational, postexposure prophylaxis (nPEP) for human immunodeficiency virus (HIV) is offered inconsistently to patients who have been sexually assaulted. This may be due to Forensic Nurse Examiner (FNE) programs utilizing diverse nPEP protocols and HIV risk assessment algorithms. This study examines factors associated with FNEs offering nPEP to patients following sexual assault at two FNE programs in urban settings. Offering nPEP is mostly driven by site-specific protocol. At Site 1, in addition to open anal or open genital wounds, the presence of injury to the head or face was associated with FNEs offering nPEP (adjusted odds ratio [AOR] 64.15, 95% confidence interval [CI] = [2.12, 1942.37]). At Site 2, patients assaulted by someone of Other race/ethnicity (non-White, non-African American) were 86% less likely to be offered nPEP (AOR 0.14, 95% CI = [.03, .72]) than patients assaulted by Whites. In addition to following site-specific protocols, future research should further explore the mechanisms influencing clinician decision making.